Economic costs of invasive alien ants worldwide - Elena Angulo; Benjamin D. Hoffmann; Liliana Ballesteros-Mejia; Ahmed Taheri; Paride Balzani; Alok Bang; David Renault; Marion Cordonnier; Céline Bellard; Christophe Diagne; Danish A. Ahmed; Yuya Watari; et al. (Biological Invasions, 2022)
Invasive ants are amongst the most destructive and widespread invaders across the globe; they can strongly alter invaded ecosystems and are responsible for the loss of native ant species. Several studies have reported that invasive ants can also lead to substantial economic costs. In this study, we search, describe and analyse 1342 reported costs of invasive ants compiled in the InvaCost database. Economic costs, reported since 1930 for 12 ant species in 27 countries, totalled US$ 51.93 billion, from which US$ 10.95 billion were incurred, and US$ 40.98 billion were potential costs (i.e., expected or predicted costs). More than 80% of total costs were associated with only two species, Solenopsis invicta and Wasmannia auropunctata ; and two countries, the USA and Australia. Overall, damage costs amounted to 92% of the total cost, mainly impacting the agriculture, public and social welfare sectors. Management costs were primarily post-invasion management (US$ 1.79 billion), with much lower amounts dedicated to prevention (US$ 235.63 million). Besides the taxonomic bias, cost information was lacking for an average of 78% of the invaded countries. Moreover, even in countries where costs were reported, such information was available for only 56% of the invaded locations. Our synthesis suggests that the global costs of invasive ants are massive but largely biased towards developed economies, with a huge proportion of underreported costs, and thus most likely grossly underestimated. We advocate for more and improved cost reporting of invasive ants through better collaborations between managers, practitioners and researchers, a crucial basis for adequately informing future budgets and improving proactive management actions of invasive ants.